Untangling intra- and interspecific effects on body size clines reveals divergent processes structuring convergent patterns in Anolis lizards - Muñoz, Martha M.; Wegener, Johanna E.; Algar, Adam C. (University of Chicago Press, 2014)
Bergmann’s rule—the tendency for body size to increase in colder environments—remains controversial today, despite 150 years of research. Considerable debate has revolved around whether the rule applies within or among species. However, this debate has generally not considered that clade-level relationships are caused by both intra- and interspecific effects. In this article, we implement a novel approach that allows for the separation of intra- and interspecific components of trait-environment relationships.We apply this approach to body size clines in two Caribbean clades of Anolis lizards and discover that their similar body size gradients are constructed in very different ways. We find inverse Bergmann’s clines—high elevation lizards are smaller bodied—for both the cybotes clade on Hispaniola and the sagrei clade on Cuba. However, on Hispaniola, the inverse cline is driven by interspecific differences, whereas intraspecific variation is responsible for the inverse cline on Cuba. Our results suggest that similar body size clines can be constructed through differing evolutionary and ecological processes, namely, through local adaptation or phenotypic plasticity (intraspecific clines) and/or size-ordered spatial sorting (interspecific clines). We propose that our approach can help integrate a divided research program by focusing on how the combined effects of intra- and interspecific processes can enhance or erode clade-level relationships at large biogeographic scales.